2016
DOI: 10.4049/jimmunol.1500257
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Stabilin-1 Suppresses the Activation of Th1 Lymphocytes

Abstract: In this study, we analyzed the putative functions of stabilin-1 in blood monocytes. Microarray analysis revealed downregulation of several proinflammatory genes in the stabilin-1high monocytes when compared with stabilin-1low monocytes. When cocultured with stabilin-1high monocytes, IFN-γ synthesis by T cells was diminished in Ag-recall assays. Knockdown of stabilin-1 in monocytes increased the synthesis of several proinflammatory molecules, including TNF-α, and supported high IFN-γ and low IL-4 and IL-5 produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 34 publications
6
48
2
2
Order By: Relevance
“…In fact, blocking Clever-1 skewed TAMs toward an immunostimulatory phenotype with increased MHC II expression and IL12p40 secretion, thus enabling efficient antigen presentation and improving tumor control by boosting infiltration of CD8 þ T cells, respectively (47). Similarly, Clever-1 knockdown in human monocytes increases their ability to reactivate T cells in antigen recall assays (11). Intriguingly, the aforementioned changes were accompanied by increased CD206 expression by MHC II high TAMs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, blocking Clever-1 skewed TAMs toward an immunostimulatory phenotype with increased MHC II expression and IL12p40 secretion, thus enabling efficient antigen presentation and improving tumor control by boosting infiltration of CD8 þ T cells, respectively (47). Similarly, Clever-1 knockdown in human monocytes increases their ability to reactivate T cells in antigen recall assays (11). Intriguingly, the aforementioned changes were accompanied by increased CD206 expression by MHC II high TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports by us and others indicate that Clever-1 also advantages tumor progression (8)(9)(10)17). However, the proposed tumorigenic mechanisms center on the paradigm of Clever-1 as an adhesion and scavenger receptor and do not explain the direct immunosuppressive functions of Clever-1 þ monocytes and macrophages we have recently described (11,18,19). Mechanistic details explaining how macrophage Clever-1 regulates innate-adaptive immune crosstalk and cancer-related inflammation are not fully understood.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Скавенджер-рецептор stabilin-1 представляет собой трансмембранный белок с небольшим цитоплазматическим доменом на С-конце, единым трансмембранным доменом и большой внеклеточной частью. Stabilin-1 рецептор участвует в захвате цитокинов, ростовых факторов, модифицированных липопротеидов, фагоцитозе апоптозных телец, компонентов экстрацеллюлярного матрикса без индуцирования провоспалительных реакций [28,29]. В ряде работ было показано, что stabilin-1 обладает противовоспалительной активностью и препятствует развитию фиброза при хроническом воспалении [29,30].…”
Section: оригинальные статьи § введениеunclassified
“…Tim-3 was required for the upregulation of these chemokines in tumoral Tregs (Figure 5C). The analysis indicated that Tim-3 was critical for the expression of an array of immune suppressive effector genes such as Calca, Fcrl6, Stab1, F2rl2, Il10, Ramp1, Cd200, Lag3, Lgals4, Fasl, Entpd1(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Interestingly, αvβ8 integrin mRNAs were also expressed at a higher level in Tim-3 sufficient Tregs, suggesting Tim-3 expression confers Treg cells the ability to activate TGF-β(39)(40)(41).…”
mentioning
confidence: 99%